Sequential transesterifications dominated reversible conversion of phragmalin-type 8/9/11-and 8/9/30-orthoesters. (28th September 2021) - Li, Haohao; Yin, Yong; Hu, Shengmou; Huang, Wansha; Kong, Lingyi; Luo, Jun
Graphical abstract: Highlights: The reversible conversion between phragmalin-type 8/9/11- and 8/9/30-orthoesters in acid condition were found. The protonated orthoester or ester group triggered sequential transesterifications may be the key steps. This research revealed a novel rearrangement mode involved multiple groups in organic synthesis. Abstract: Orthoesters based on phragmalin-type limonoid from Meliaceae family is an important branch of plant orthoesters, and it is mainly existed as 1/8/9-, 8/9/11-, 8/9/14-, or 8/9/30-types. In the process of exploring the biogenetic pathway of the orthoester moiety in phragmalins, the reversible conversion between 8/9/11-orthoerter (tabularisin A, 1 ) and 8/9/30-orthoester (tabularisin C, 2 ) under acid-catalyzed condition were found and optimized. The protonated orthoester or ester group triggered sequential transesterifications may be the key steps of this reversible rearrangement. This research not only revealed a novel rearrangement mode involving multiple groups in organic synthesis, but also suggested the close biosynthetic relationship between 8/9/11- and 8/9/30-phragmalin-type orthoesters.